2017
DOI: 10.5414/np300993
|View full text |Cite
|
Sign up to set email alerts
|

Validation of nuclear STAT6 immunostaining as a diagnostic marker of meningeal solitary fibrous tumor (SFT)/hemangiopericytoma

Abstract: STAT6 immunohistochemistry is a robust method to verify diagnosis of SFT/hemangiopericytoma and should therefore be included in the diagnostic work-up of meningeal tumors. In singular cases, weak and focal STAT6 expression may lead to false-negative evaluation and may prompt further molecular work-up.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Literature from the past 5 years was searched, and we found that STAT6 immunohistochemistry has high specificity for SFT and that the diagnostic value of strong and diffuse nuclear expression of STAT6 in SFT has been proven. [18][19][20] It was also found that STAT6 is a dependable marker to differentiate SFT from myofibromas. 21 At the same time, follicular lymphomaassociated STAT6 mutations facilitate nuclear residency of STAT6, 22 while nuclear localization of STAT6 is also dramatically increased in Kaposi's sarcoma tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Literature from the past 5 years was searched, and we found that STAT6 immunohistochemistry has high specificity for SFT and that the diagnostic value of strong and diffuse nuclear expression of STAT6 in SFT has been proven. [18][19][20] It was also found that STAT6 is a dependable marker to differentiate SFT from myofibromas. 21 At the same time, follicular lymphomaassociated STAT6 mutations facilitate nuclear residency of STAT6, 22 while nuclear localization of STAT6 is also dramatically increased in Kaposi's sarcoma tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Sarcomatoid carcinomas typically show positivity for CK [7], which was not the case in our patient. Absence of STAT-6 goes against a diagnosis of meningeal hemangiopericytoma [8]. Chromogranin and synaptophysin studies which are usually positive in paragangliomas were not available; however, imaging was not suggestive of that [9].…”
Section: Discussionmentioning
confidence: 99%
“…IHC for STAT6 is a reliable marker to confirm the SFT/HPC destination. 12,13 Our study, included the SFT/HPC cases that were confirmed by STAT6, IHC, or next generation sequencing to avoid the diagnostic ambiguity. NAB2-STAT6 fusion is the driver mutation of SFT/HPC and the fusion constitutively activates EGR1.…”
Section: Discussionmentioning
confidence: 99%